2009
DOI: 10.1152/ajpendo.90459.2008
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate induces intestinal mucositis and alters gut protein metabolism independently of reduced food intake

Abstract: One of the main secondary toxic side effects of antimitotic agents used to treat cancer patients is intestinal mucositis. This one is characterized by compromised digestive and absorptive functions, barrier integrity, and immune competence. At the same time, food intake is decreased, which may induce intestinal damages per se. The aim of the study was to characterize which alterations are specific to methotrexate, independently of the anorexic effect of the drug. Male Sprague-Dawley rats received subcutaneousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 40 publications
7
51
0
2
Order By: Relevance
“…Proteasome activities were evaluated as previously described (3,28,29) by using spectrofluorimetry on a microtiter plate fluorometer (Mithras LB 940; Berthold Technologies) with fluorogenic proteasome substrates Suc-LLVY-MCA (PSIII; Calbiochem) for chymotrypsin-like activity, Boc-LSTR-MCA (Sigma Aldrich) for trypsin-like activity, and Z-LLE-MCA (Sigma Aldrich) for caspase-like or peptidyl-glutamyl peptidehydrolyzing activity in the presence or absence of proteasome inhibitor (10 mmol/L MG132; Sigma Aldrich). Thus, proteasome activity was calculated by using the difference between the activity measured in the absence of MG132 proteasome inhibitor and the activity measured in the presence of MG132 proteasome inhibitor.…”
Section: Proteasome Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteasome activities were evaluated as previously described (3,28,29) by using spectrofluorimetry on a microtiter plate fluorometer (Mithras LB 940; Berthold Technologies) with fluorogenic proteasome substrates Suc-LLVY-MCA (PSIII; Calbiochem) for chymotrypsin-like activity, Boc-LSTR-MCA (Sigma Aldrich) for trypsin-like activity, and Z-LLE-MCA (Sigma Aldrich) for caspase-like or peptidyl-glutamyl peptidehydrolyzing activity in the presence or absence of proteasome inhibitor (10 mmol/L MG132; Sigma Aldrich). Thus, proteasome activity was calculated by using the difference between the activity measured in the absence of MG132 proteasome inhibitor and the activity measured in the presence of MG132 proteasome inhibitor.…”
Section: Proteasome Activitiesmentioning
confidence: 99%
“…In some pathophysiologic conditions, protein turnover is altered and may contribute to intestinal or systemic diseases. Gut protein metabolism can be affected by nutritional state (3)(4)(5) or nutritional interventions (1,4,(6)(7)(8). Amino acids, as constituents of proteins and signaling molecules, have been extensively tested in vitro and in vivo, but results have appeared to be model and condition dependent (9).…”
Section: Introductionmentioning
confidence: 99%
“…It could also be argued that decreases in serum citrulline levels could indeed reflect the decreases in the patient's food intake, as reductions in and withdrawal from food is commonly observed in bone marrow transplant patients. 63 More recently, a study by Boukhettala et al 64 suggested that a reduction in food intake did not mimic citrulline levels observed in MTX-treated rats. However, this finding has yet to be confirmed in humans, or indeed, in cancer patients.…”
Section: Methods For Assessing Small Intestinal Functionmentioning
confidence: 98%
“…In the placebo diet, whey proteins and TGFb-rich casein were replaced by TGFb-free casein and free glutamine by free alanine (Table 1). Mucositis was induced by three subcutaneous injections of 2.5 mg/kg MTX (Teva Pharma, Courbevoie, France) for 3 consecutive days (day 0, 1 and 2) as previously described [3,4]. Control rats received injections of saline (0.9%).…”
Section: Methodsmentioning
confidence: 99%
“…The pathophysiology of mucositis involves tissue lesions and secondary inflammatory response [2]. In rats, we recently reported that MTX treatment alters intestinal barrier function and protein metabolism [3] independent of the anorectic effect of MTX [4]. Indeed, MTX treatment was associated with a decrease of protein synthesis [4] and an increase of lysosomalmediated proteolysis in jejunal mucosa [3,4], which may contribute to the disruption of the gut barrier.…”
Section: Introductionmentioning
confidence: 99%